Technological Development and The Dynamics of Juwana’s Fisherman Social Structure - Situmeang, Widya Hasian; A Kinseng, Rilus; P Lubis, Djuara (Sodality: Jurnal Sosiologi Pedesaan, 2020)
Changes created by technological developments are not only about material changes, but are also closely related to changes in social structure in the community as users and consequences recipients of these technologies application. The capture fisheries community is one of many communities that have also experienced the development of fishing technology. It cannot be denied that technological sophistication is driving the production of the fishing community. However, this increase is not necessarily followed by an increase in welfare for the community. This paper aims to examine technological developments and changes in social structure in the fishing community in Juwana, especially in Bendar Village and Bajomulyo Village, and identify their implications for community welfare. The research that underlies this paper is conducted using qualitative methods. The results showed that the development of technology brought changes in social structure in the fishing community. The economy and welfare of the community are getting better due to the efficiency of fishing with the latest technology. Solidarity that grows in the fishing communities in the two villages, is a key factor in preventing inter-class exploitation by maintaining the position of members of the upper stratification of fisher community from competition with upper strata outside the community, as well as providing a space for community members from the middle and lower strata to carry out social upward mobility. Keywords: fisher, fishing technology, social structure, solidarity, social mobility.